Evaluation of patients admitted to the emergency department with the suspect of acute renal colic with the modified STONE score - Güllüpınar, Birdal; Ayvat, Pınar; Ünlüer, Erden Erol; Koran, Serhat (Emergency Medicine Physicians Association of Turkey, 2022)
Aim: Renal colic pain is one of the most common agonizing forms of pain that is frequently treated in emergency departments. Computed tomography (CT), which is used for the detection of kidney stones, is a costly application. Therefore, scoring systems that predict stone have been developed. This study was conducted to investigate the diagnostic accuracy of the Modified STONE Score (MSS) to predict stones. Materials and Methods: Among those who applied to the emergency department with renal colic pain, patients with CT were examined. Three hundred and thirty-seven patients included in the study were divided into two groups as those with and without kidney stones. It was examined whether there was a difference between these two groups in terms of personal, seasonal, laboratory findings and MSS. Results: We found that ureteral stone history, pain duration less than 6 hours, presence of hematuria and nausea/vomiting, C-reactive protein (CRP) value below 0.5 mg/dL, The MSS above 9, age <= 50 years were factors that increase stone. The MSS was significantly high in the stone-detected group. When the STONE score is calculated for all patients and divided into three groups (low, moderated, and high modified STONE scores), the prevalence of ureteral stones increases towards the high MSS group. Conclusion: We found that the modified STONE score was quite successful in predicting ureteral stones. We determined that emergency physicians can diagnose stones using this score and avoid unnecessary CT. The diagnostic value of this score may increase when nausea/ vomiting factor is added.
Keywords: Modified STONE Score; Urinary Tract Stones; Emergency Departments